The Implementation of Operational Risk Management Using the HIRARC Method (Hazard Identification, Risk Assessment, and Risk Control) in the Human Resources and Correspondence Division at PPSDM Migas - Dzurrotun Nasikhah; Mohammad Khusnu Milad (JURNAL MANAJEMEN RISIKO, 2026)
Risk management has become an essential component in ensuring organizational effectiveness, particularly within government institutions that manage public services and administrative accountability. The Human Resources and Correspondence Division at PPSDM Migas plays a strategic role in handling personnel administration, certification documentation, and official correspondence processes. The complexity of these administrative activities creates potential operational risks, including human error, document mismanagement, delays in correspondence processing, and data inaccuracies, which may affect institutional credibility and service quality. This study aims to identify, assess, and control operational risks within the Human Resources and Correspondence Division using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The research applies a descriptive qualitative approach supported by a literature review and observational data. Risk assessment is conducted by evaluating likelihood and severity levels to determine risk categories. The findings indicate that several identified risks fall into Moderate and High categories, particularly those related to documentation errors and delays in administrative processing. Therefore, risk control strategies such as digitalization of records, strengthening standard operating procedures (SOPs), and capacity-building programs for staff are recommended to reduce risks to acceptable levels. Keywords: Operational Risk Management; HIRARC; Human Resources Administration; Correspondence Management; Government Institution; Risk Control Strategy